Pendampingan Petani Stroberi di Desa Serang, Karangreja, Purbalingga, Jawa Tengah Dalam Manajemen Kesehatan Tanaman Melalui KKN-PPM Universitas Gadjah Mada: Perlunya Bibit Stroberi Sehat dan Peningkatan Keterlibatan Petani dalam Kegiatan Kelompok - Ani Widiastuti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Serang village, Karangreja, Purbalingga is a plateau area with an altitude of about 650—1300 above sea level, has high rain fall around 6,240 mm with an average temperature of 20°C. This village is a leading commodity for strawberry with plant area has ever reached 64ha. The main problem faced by the strawberries farmers in the village of Serang is a problem of plant health management to support the production, especially on rainy season. Awareness about healthy seedlings as a main aspect of plant health managed mental so needs to be improved. Therefore, a collaborative research and empowerment of farmers is arranged to assist farmers in identifying problems and how to solve by their own that in maintaining the health of the strawberry plant. This project was conducted firstly in 2013 by KKN-PPM UGM students in collaboration with Ibaraki University, Japan, Bappeda Purbalingga, and government of Purbalingga Regency. The methods were direct survey of field, farmers interview, extension and discussion among students and farmers in formal and informal meetings, then continued by some trainings. The informal meetings were conducted on site in farmers field and it was assumed that although it was not really efficient in time and energy, but it was effective for farmers to emerge their idea on identifying problems and solving methods therefore the farmers empowerment was done in this matter. Due to problem identification activities, it was known that healthy seedlings were the main problem in strawberry cultivation there. The involvement of farmers in the group also needs to be improved as a forum for exchange of ideas to move forward together. As this activity in 2013 is the first project of long-term project to contribute for Serang farmers in plant health management. Some creative methods need to be designed and improved in the future.